Danse macabre [compact disc] - Angelis, Victoria De (BMG Rights Management, 2023)
Duran Duran returns with their new album, Danse Macabre. The 13-song collection features three brand new songs, haunting covers of songs by artists such as Billie Eilish, Talking Heads, the Rolling Stones, and the Specials, and new versions of classics from their own catalog.